Tools for Machine-Aided Translation: The CMU TWS - Nirenburg, Sergei (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1992)
AbstractInteractive user environments have been a central efficiency-enhancing feature of many modern computer applications, including natural processing. There are two major kinds of people for whom environments can and must be constructed — developers and end users. Developers need help with a variety of knowledge acquisition tasks, such as dictionary and grammar writing. End users (e.g., technical writers or translators) look for efficiency enhancements beyond the level of word processing support. There are two approaches to building interactive tools. A dedicated workstation can be developed for each of the required functionalities. Alternatively, workstations can be configured as sets of application routines attached to a universal user interface. In this paper, we describe a general-purpose user environment, under development at the Center for Machine Translation of Carnegie Mellon University. This environment can support several machine-aided human translation configurations and a human-aided machine translation configuration. It also supports knowledge acquisition for machine translation and other NLP systems.